2018
DOI: 10.1021/acs.orglett.8b03159
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Metal-Free Aza-Heck Reactions of Terminal Alkenes Catalyzed by Phosphine Selenides

Abstract: Phosphine selenides are introduced as an alternate class of selenium-based catalysts for the aza-Heck reaction of alkenes. Using these catalysts, a range of terminal alkenes react with NFBS to give oxidative amination products. Judicious choice of phosphine ligand gives greater regio-and stereoselectivity than with diphenyl diselenide, enabling the selective formation of E terminal enimides in high yields. Isotope-labeling experiments and measurements of kinetic isotope effects reveal that the reaction occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In a similar manner, analogous complexes of these ligands with selenium, i.e., phosphine selenides and selenoureas, which are trivial to generate from the corresponding phosphines and imidazolium salts, might also serve as more effective catalysts. Indeed, we and others have recently shown that these complexes can be used to control the selectivity of selenium-catalyzed reactions. Gratifyingly, phosphine selenide catalysts did afford the desired allylic amination product, with 15 mol % tricyclohexylphosphine selenide (Cy 3 PSe) proving to be the most convenient and effective catalyst. The quantity of catalyst could be reduced further to 5 mol % with only a moderate drop in yield.…”
Section: Resultsmentioning
confidence: 96%
“…In a similar manner, analogous complexes of these ligands with selenium, i.e., phosphine selenides and selenoureas, which are trivial to generate from the corresponding phosphines and imidazolium salts, might also serve as more effective catalysts. Indeed, we and others have recently shown that these complexes can be used to control the selectivity of selenium-catalyzed reactions. Gratifyingly, phosphine selenide catalysts did afford the desired allylic amination product, with 15 mol % tricyclohexylphosphine selenide (Cy 3 PSe) proving to be the most convenient and effective catalyst. The quantity of catalyst could be reduced further to 5 mol % with only a moderate drop in yield.…”
Section: Resultsmentioning
confidence: 96%
“…Herein, as an advancement of our previous efforts on aminative functionalizations with NFSI as an amino donor, , as well as our continuous interest in construction and functionalization of heterocycles, we would like to disclose a synergistic copper/TEMPO-catalyzed formal aza-Wacker cyclization at room temperature according to the proposed N – N radical relay as shown in Scheme c. The primary challenge of this novel strategy for aza-Wacker-type cyclization is attributed to the high reactivity of the imidyl NCR A generated from NFSI, which might readily react with the alkene CC double bond , instead of the carbamate or amide N–H bond, leading to undesired intermolecular allylic imidation products . It is thus crucial to delicately control such chemo-selectivity.…”
mentioning
confidence: 99%
“…In this reaction, N−S bond was broken, and C(sp 3 )−S and C=O bonds were formed. When the reaction was carried out with a mixture of 10 mol % of selenium powder and 10 mol % of PPh 3 as the catalyst, [21] the yield rose to 22 % (entry 2). The use of PhSeBr as the catalyst could significantly promote the yield (from 12 % to 33 %, entry 3), while the other monoselenide pre‐catalyst PhSeCl decreased the yield (entry 4).…”
Section: Methodsmentioning
confidence: 99%